Photodynamic therapy for oral cancer: Mechanisms, efficacy, and clinical applications - Shyamaladevi Babu; Madhan Krishnan (Oral Oncology Reports)
Photodynamic therapy (PDT) has emerged as a promising therapeutic approach for oral cancer, characterized by its ability to selectively target malignant cells while minimizing damage to surrounding healthy tissues. This review synthesizes current knowledge on PDT's clinical applications in oral cancer treatment, emphasizing its efficacy in managing early-stage cancers and precancerous lesions with favorable outcomes. PDT's non-invasive nature and potential for preserving critical anatomical functions make it particularly suitable for cases where surgical intervention may pose higher risks or affect quality of life adversely. Ongoing research efforts focus on refining PDT through advancements in photosensitizer formulations and optimizing light delivery systems. These developments aim to enhance treatment efficacy, extend PDT's applicability to deeper tumors, and address challenges such as treatment resistance. Furthermore, researchers are investigating personalized treatment strategies designed to enhance therapeutic results and reduce potential side effects for each patient's specific profile. Future directions include exploring synergistic combinations of PDT with chemotherapy and immunotherapy, aiming to potentiate therapeutic responses and improve long-term survival rates. By integrating technological innovations with personalized medicine strategies, PDT holds promise as a cornerstone in the multidisciplinary management of oral cancer, offering new avenues for enhancing patient care and treatment outcomes in clinical practice.